Validation of Dracula trignopetala (Orchidaceae: Pleurothallidinae) with an English diagnosis and description - Doucette, Alfonso (Phytotaxa, 2012)
Dracula trigonopetala was first proposed on 3 January 2012 in an electronic (pdf) file released by OrchideenJournal (Meyer et al. 2012a). In this, the name was associated with a diagnosis and description in English, but the pdf lacked a volume number and pagination. Thus, the name was not effectively published. When a printed copy of the journal was released on 15 August 2012 (Meyer et al. 2012b), the diagnosis and description were in German, not English or Latin. As a result, the name was effectively published but not valid as it was a nomen nudum. As the species is worthy of recognition, D. trigonopetala is validated here.